Method for detecting defects in porous polymer substrates for separation membranes in advance
Patent Information
- Application Number
- JP2023519126
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-06
- Filing Date
- 2022-04-06
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2042-04-06
AI Technical Summary
【0020】 本発明の一具現例による分離膜用多孔性高分子基材の不良品事前検出方法は、多孔性高分子基材の少なくとも一面上に有機-無機複合多孔性層を備えた分離膜を最終的に製造した後に分離膜の通気度特性などの不良品を確認する従来の方法と比べて、有機-無機複合多孔性層を形成する前に、分離膜素材である多孔性高分子基材の段階において多孔性高分子基材のイメージ上の相違点を用いて明確に不良品を検出することができる。すなわち、電子顕微鏡(SEM)で観察して得た多孔性高分子基材のイメージを用いて気孔分布均一度指数(PDI)の平均値を定量化し、補正して得た結果値と所定基準値との大小比較を通じて多孔性高分子基材の良品及び不良品を検出できるため、従来の分離膜段階で不良品を確認する方法に比べて時間及びコストを著しく節減することができる。
Smart Images

Figure 0007636528000002 
Figure 0007636528000003 
Figure 0007636528000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for detecting defects in a porous polymer substrate for a separation membrane in advance.
[0002] This application claims priority to Korean Patent Application No. 10-2021-0044855, filed on April 6, 2021, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] In recent years, interest in energy storage technology has been increasing. As the fields of application expand to include mobile phones, camcorders, and laptops, as well as the energy of electric vehicles, efforts in the research and development of electrochemical elements have been increasingly realized. Electrochemical elements are the field that has attracted the most attention from this perspective, and in particular, the development of rechargeable secondary batteries has attracted attention. In recent years, in the development of such batteries, research and development related to the design of new electrodes and batteries has been conducted in order to improve the capacity density and specific energy.
[0004] Among the secondary batteries currently in use, lithium secondary batteries, developed in the early 1990s, have been attracting attention due to their advantages of high operating voltage and significantly higher energy density compared to conventional batteries that use aqueous electrolytes, such as Ni-MH, Ni-Cd, and sulfuric acid-lead batteries.
[0005] Such a lithium secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator, among which the separator is required to have insulating properties for separating and electrically insulating the positive electrode and the negative electrode, and high ionic conductivity for increasing the permeability of lithium ions based on high porosity.
[0006] Such a separation membrane may be applied in the form of a porous polymer substrate prepared by kneading a polymer such as polyolefin with a diluent, extruding and stretching the mixture to form a film, and then extracting the diluent using a solvent or the like to form pores. A composite separation membrane may also be applied in the form of a composite porous membrane having an organic-inorganic composite porous layer including a binder polymer and inorganic particles on at least one surface of the porous polymer substrate.
[0007] In this case, the properties of the porous polymer substrate used in the secondary electron separator can be adjusted in various ways depending on the process conditions during manufacture. In particular, the pore structure of the porous polymer substrate, which is the path of lithium ions, can also be varied in various ways depending on the process conditions.
[0008] In particular, if excessive heat is applied during the stretching process, problems may occur such as the pore size of the final porous polymer substrate becoming large, the surface morphology of the porous polymer substrate becoming non-uniform, or the polymer fibrils contained in the porous polymer substrate becoming thick, etc. When the porous polymer substrate is used in the form of a composite separator, these problems include an excessive increase in the ventilation time of the separator after the formation of the organic-inorganic composite porous layer.
[0009] This cannot be observed by measuring the physical properties of a single item, such as the aeration time of the separation membrane. In particular, when measuring the pore size using a capillary flow porometer, the measured values vary from one measurement site to another, which is disadvantageous in terms of quality control.
[0010] Therefore, in order to control the quality of the porous polymer substrate that is the material for the separation membrane, a method is required that can easily identify products with defective pore sizes (non-uniform morphology). Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a method for pre-detecting defects in a porous polymer substrate for a separation membrane, which can easily check for defects in appearance of the separation membrane in order to control the quality. [Means for solving the problem]
[0012] An aspect of the present invention provides a method for pre-detecting defects in a porous polymer substrate for a separation membrane, according to the following embodiment.
[0013] According to the first embodiment, Selecting a porous polymer substrate having a large number of pores to detect whether the substrate is good or bad; Obtaining an image of the selected porous polymer substrate by observing the selected porous polymer substrate with a scanning electron microscope (SEM); Quantifying an average pore distribution index (PDI) using the acquired image of the porous polymer substrate; correcting the average value of the quantified pore distribution uniformity index to obtain an average value of the corrected pore distribution uniformity index; determining whether the average value of the corrected pore distribution uniformity index is 60 a.u. (arbitrary unit) or less; classifying the porous polymer substrate as a non-defective product when the average value of the corrected pore distribution uniformity index is confirmed to be 60 a.u. or less, and classifying the porous polymer substrate as a defective product when the average value of the corrected pore distribution uniformity index is confirmed to be more than 60 a.u.
[0014] According to the second embodiment, in the first embodiment, The step of quantifying the average value of the pore distribution uniformity index may be a step of quantifying an image of the porous polymer substrate measured by a scanning electron microscope (SEM) through mathematical theory (Euclidean distance measurement method) and a computer engineering algorithm.
[0015] According to the third embodiment, in the second embodiment, Quantifying the average pore distribution uniformity index may include calculating the pore distance and pore size from an image of the porous polymer substrate measured by scanning electron microscope (SEM).
[0016] According to the fourth embodiment, in the second or third embodiment, Quantifying the average value of the pore distribution uniformity index, obtaining a 2-D binary image by dividing the pixels of a raw image of the porous polymer substrate measured by a scanning electron microscope (SEM) into pixels representing a region of a plurality of polymer fibrils adjacent to or intersecting each other and pixels representing pore regions formed between the plurality of polymer fibrils; distance transforming the two-dimensional binary image using a computer Euclidean distance transform method; and applying a local maxima operation to the distance transformed image to extract distance transformed values of all pixels of the image and statistically process the distance transformed values.
[0017] According to the fifth embodiment, in one of the first to fourth embodiments, The step of correcting the average value of the quantified pore distribution uniformity index (pre-correction average PDI) and obtaining the average value of the corrected pore distribution uniformity index (corrected average PDI) can be calculated by the following Equation 1. [Formula 1] Corrected average PDI=Pre-correction average PDI×(1 / η) In Equation 1, η is a correction factor and is defined as η=(number of polymer fibril pixels) / (number of total image pixels).
[0018] According to the sixth embodiment, in one of the first to fifth embodiments, A separator obtained by coating and drying a slurry containing inorganic particles, a binder polymer, and a dispersion medium on at least one surface of the porous substrate classified as a non-defective product to form an organic-inorganic composite porous layer may have an air permeability of 600 sec / 100 cc or less.
[0019] According to the seventh embodiment, in one of the first to sixth embodiments, If the average value of the corrected pore distribution uniformity index is confirmed to be 40 a.u. or less, the product may be classified as a non-defective product, and if the average value of the corrected pore distribution uniformity index is confirmed to be more than 40 a.u., the product may be classified as a defective product. Effect of the Invention
[0020] The method for pre-detecting defects in a porous polymer substrate for a separation membrane according to an embodiment of the present invention can clearly detect defects using differences in the image of the porous polymer substrate, which is a material for a separation membrane, before forming an organic-inorganic composite porous layer, compared to a conventional method for detecting defects in the air permeability of a separation membrane after finally manufacturing a separation membrane having an organic-inorganic composite porous layer on at least one surface of the porous polymer substrate. That is, the average value of the pore distribution uniformity index (PDI) is quantified using an image of the porous polymer substrate obtained by observation with a scanning electron microscope (SEM), and the resultant value obtained by correcting the quantification is compared with a predetermined reference value to detect pass / fail of the porous polymer substrate, thereby significantly reducing time and cost compared to a conventional method for detecting defects at the separation membrane stage.
[0021] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention together with the content of the invention, and therefore the present invention should not be interpreted as being limited only to the matters described in the drawings. [Brief description of the drawings]
[0022] [Figure 1a] 1 is a SEM image of the porous polyolefin substrate prepared in Preparation Example 1. [Figure 1b] 1 is an image showing a distance conversion result of the porous polyolefin substrate prepared in Preparation Example 1. [Figure 1c] FIG. 2 is a graph showing the average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrate prepared in Preparation Example 1 and the corrected pore distribution uniformity index. [Figure 2a] 1 is a SEM image of the porous polyolefin substrate prepared in Preparation Example 2. [Figure 2b] 1 is an image showing a distance conversion result of the porous polyolefin substrate prepared in Preparation Example 2. [Figure 2c] FIG. 2 is a graph showing the average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrate prepared in Preparation Example 2 and the corrected pore distribution uniformity index. [Figure 3a] 1 is a SEM image of the porous polyolefin substrate prepared in Preparation Example 3. [Figure 3b] 1 is an image showing a distance conversion result of the porous polyolefin substrate prepared in Preparation Example 3. [Figure 3c] FIG. 2 is a graph showing the average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrate prepared in Preparation Example 3 and the corrected pore distribution uniformity index. [Figure 4a] 1 is a SEM image of the porous polyolefin substrate prepared in Preparation Example 4. [Figure 4b] 1 is an image showing a distance conversion result of the porous polyolefin substrate prepared in Preparation Example 4. [Figure 4c] FIG. 1 shows the average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrate prepared in Preparation Example 4, and a graph of the corrected pore distribution uniformity index. [Figure 5a] 1 is a SEM image of the porous polyolefin substrate prepared in Preparation Example 5. [Figure 5b] 1 is an image showing a distance conversion result of the porous polyolefin substrate prepared in Preparation Example 5. [Figure 5c] FIG. 1 shows the average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrate prepared in Preparation Example 5, and a graph of the corrected pore distribution uniformity index. [Figure 6a] 1 is a raw image of a porous polyolefin substrate produced in Production Example 1. [Figure 6b] 1 is a two-dimensional binary image of the porous polyolefin substrate produced in Production Example 1. [Figure 6c] 1 is a graph showing the average quantified pore distribution uniformity index (average uncorrected PDI) of the porous polyolefin substrate produced in Production Example 1. [Figure 6d] 1 is a graph showing the average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrate prepared in Preparation Example 1. [Figure 7a] 1 is a raw image of a porous polyolefin substrate produced in Production Example 4. [Figure 7b] 2 is a two-dimensional binary image of the porous polyolefin substrate produced in Production Example 4. [Figure 7c] 1 is a graph showing the average quantified pore distribution uniformity index (average uncorrected PDI) of the porous polyolefin substrate produced in Production Example 4. [Figure 7d] 1 is a graph showing the average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrate prepared in Preparation Example 4. [Figure 8] FIG. 13 shows an example of a sequence of steps for quantifying the average pore distribution uniformity index from raw images. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will be described in detail below. The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventors themselves can appropriately define the concepts of terms in order to best describe the invention.
[0024] According to an embodiment of the present invention, a method for detecting defects in a porous polymer substrate for a separation membrane in advance includes: Selecting a porous polymer substrate having a large number of pores to detect whether the substrate is good or bad; Obtaining an image of the selected porous polymer substrate by observing the selected porous polymer substrate with a scanning electron microscope (SEM); Quantifying an average pore distribution index (PDI) using the acquired image of the porous polymer substrate; correcting the average value of the quantified pore distribution uniformity index to obtain an average value of the corrected pore distribution uniformity index; determining whether the average value of the corrected pore distribution uniformity index is 60 a.u. or less; If the average value of the corrected pore distribution uniformity index is confirmed to be 60 a.u. or less, the product is classified as a good product, and if the average value of the corrected pore distribution uniformity index is confirmed to be more than 60 a.u., the product is classified as a defective product.
[0025] First, a porous polymer substrate having a large number of pores is selected to detect whether it is a good or bad product.
[0026] Here, the porous polymer substrate refers to a separation membrane material before the organic-inorganic composite porous layer is formed in a separation membrane having an organic-inorganic composite porous layer. The porous polymer substrate has a plurality of polymer fibers arranged parallel to each other or crossing each other, and includes a large number of pores formed between the plurality of polymer fibers, and may include a fiber region and a pore region.
[0027] Specifically, the porous polymer substrate may be a porous polymer film substrate or a porous polymer nonwoven fabric substrate.
[0028] The porous polymer film substrate may be a porous polymer film made of a polyolefin such as polyethylene or polypropylene, and such a polyolefin porous polymer film substrate exhibits a shutdown function at a temperature of, for example, 80 to 130°C.
[0029] In this case, the polyolefin porous polymer film may be formed by using a polyolefin polymer such as polyethylene (e.g., high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene), polypropylene, polybutylene, polypentene, etc., either alone or in combination of two or more of these.
[0030] In addition, the porous polymer film substrate may be manufactured by forming various polymers such as polyester in addition to polyolefin into a film shape. In addition, the porous polymer film substrate may be formed in a structure in which two or more film layers are laminated, and each film layer may be formed from the above-mentioned polymers such as polyolefin and polyester alone or a mixture of two or more of them.
[0031] In addition, the porous polymer film substrate and the porous nonwoven fabric substrate may be formed from a polymer selected from the group consisting of polyolefin, polyester (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, etc., either alone or in combination.
[0032] The thickness of the porous polymer substrate is not particularly limited, but may be 1 to 100 μm, more particularly 5 to 50 μm, and the pore size and porosity of the porous polymer substrate are also not particularly limited, but may be 0.01 to 50 μm and 10 to 95%, respectively.
[0033] As the porous polymer substrate, a porous polyolefin substrate may be particularly used, in which the polyolefin may include polyethylene; polypropylene; polybutylene; polypentene; polyhexene; polyoctene; a copolymer of two or more of ethylene, propylene, butene, pentene, 4-methylpentene, hexene, and octene; or a mixture thereof.
[0034] In particular, the polyethylene may be low density polyethylene (LDPE), linear low density polyethylene (LLDPE), high density polyethylene (HDPE), etc., among which high density polyethylene having a high crystallinity and a high melting point of the resin may be mainly used.
[0035] In an embodiment of the present invention, the weight average molecular weight of the polyolefin may be 200,000 to 1,500,000, 220,000 to 1,000,000, or 250,000 to 800,000. In the present invention, a high molecular weight polyolefin having a weight average molecular weight of 200,000 to 1,000,000 is used as a starting material for producing a separation membrane, thereby ensuring the uniformity and membrane production process of the separation membrane, and finally obtaining a separation membrane having excellent strength and heat resistance.
[0036] Next, the selected porous polymer substrate is observed under a scanning electron microscope (SEM) to obtain an image of the porous polymer substrate.
[0037] According to one embodiment of the present invention, an image of the porous polymer substrate is obtained using a scanning electron microscope (SEM) at 5 kV, 10 μA, and a magnification of 20,000.
[0038] The obtained images of the porous polymer substrate are used to quantify the average pore distribution index (PDI).
[0039] In the step of quantifying the average value of the pore distribution uniformity index, the image of the porous polymer substrate measured by a scanning electron microscope (SEM) can be quantified through mathematical theory (Euclidean distance measurement method) and computer engineering algorithms.
[0040] The step of quantifying the average value of the pore distribution uniformity index may include calculating the pore distance and pore size (area ratio) from an image of the porous polymer substrate measured by scanning electron microscope (SEM).
[0041] According to one embodiment of the present invention, the step of quantifying the average value of the pore distribution uniformity index may include the steps of: obtaining a 2-D binary image by dividing pixels of a raw image of the porous polymer substrate measured by a scanning electron microscope (SEM) into pixels representing a plurality of polymer fibril regions that are adjacent to or intersecting with each other and pixels representing pore regions formed between the plurality of polymer fibrils; distance transforming the 2-D binary image using a computer Euclidean distance transform method; and applying a local maxima operation to the distance transformed image to extract and statistically process distance transformed values of all pixels of the image.
[0042] In this case, the step of extracting and statistically processing distance transform values of all pixels of the image by applying a local maxima operation to the distance transformed image may include: separating the distance transformed image into segments using local minimas of distance transform values as boundaries; and filling local maximas of the distance transform values of the separated segments with the distance transform values of all pixels of the separated segments, and extracting and statistically processing the entire distance transform value of each pixel.
[0043] An example of the sequence of steps for quantifying the average pore distribution uniformity index from such raw images is shown in Figure 8 .
[0044] Thereafter, the average value of the quantified pore distribution uniformity index is corrected to obtain an average corrected pore distribution uniformity index.
[0045] A porous polymer substrate is composed of the arrangement of polymer fibrils that compose it and the pores formed between adjacent polymer fibrils. In this case, the distribution and area of the pore regions can affect the physical properties required for the porous polymer substrate as a separation membrane material, such as the air permeability.
[0046] That is, even if the porous polymer substrate has the same average quantified pore distribution uniformity index, the physical properties of the porous polymer substrate may differ depending on the area of the pore region formed in the porous polymer substrate. Therefore, in the present invention, the average quantified pore distribution uniformity index is corrected.
[0047] Specifically, the quantified pore distribution uniformity index has the limitation that it cannot reflect the area characteristics of pores because it calculates the distance from pores based on pixels corresponding to fibrils. The ratio of the number of polymer fibril pixels to the number of total image pixels is defined as a correction factor (η), and the average pore distribution uniformity index is divided by the correction factor, so that when pores are large and numerous, the average pore distribution uniformity index can be made larger to reflect the influence of the pore area.
[0048] The step of correcting the average value of the quantified pore distribution uniformity index (pre-correction average PDI) and obtaining the average value of the corrected pore distribution uniformity index (corrected average PDI) can be calculated by the following Equation 1.
[0049] [Formula 1] Corrected average PDI=Pre-correction average PDI×(1 / η) In Equation 1, η is a correction factor and is defined as η=(number of polymer fibril pixels) / (number of total image pixels).
[0050] It is checked whether the average value of the corrected pore distribution uniformity index is 60 a.u. or less. If the average value of the corrected pore distribution uniformity index is 60 a.u. or less, the product is classified as a non-defective product, and if the average value of the corrected pore distribution uniformity index is more than 60 a.u., the product is classified as a defective product.
[0051] According to an embodiment of the present invention, whether the average value of the corrected pore distribution uniformity index is 40 a.u. or less can be used as a criterion for determining whether the porous polymer substrate is good or bad.
[0052] In the case of a porous polymer substrate having an average corrected pore distribution uniformity index of 60 a.u. or less, the air permeability of the porous polymer substrate before the formation of the organic-inorganic composite porous layer may be at the same level as that of a porous polymer substrate having an average corrected pore distribution uniformity index of more than 60 a.u., but the air permeability of the separator obtained after the formation of the organic-inorganic composite porous layer is such that the porous polymer substrate having an average corrected pore distribution uniformity index of 60 a.u. or less exhibits significantly better air permeability characteristics than the porous polymer substrate having an average corrected pore distribution uniformity index of more than 60 a.u. That is, in a porous polymer substrate having an average corrected pore distribution uniformity index of 60 a.u. or less, the pores located within the porous polymer substrate are uniformly distributed over a uniform area. Therefore, even when an organic-inorganic composite porous layer is introduced onto at least one surface of the porous polymer substrate, which creates severe conditions for maintaining breathability, the porous polymer substrate exhibits performance suitable for application to a separator for a secondary battery without significant deterioration in breathability characteristics.
[0053] In the present invention, the porous polymer substrate to be detected as defective can be used as a separation membrane by itself, but in fields requiring additional thermal stability, an organic-inorganic composite porous layer can be provided on at least one side to produce a separation membrane with enhanced stability.
[0054] The separator having enhanced stability by providing an organic-inorganic composite porous layer on at least one surface thereof comprises an organic-inorganic composite porous layer located on at least one surface of a porous polymer substrate, the organic-inorganic composite porous layer including a plurality of inorganic particles and a binder polymer located on some or all of the surfaces of the inorganic particles to connect and fix the inorganic particles to each other.
[0055] The binder polymer may be a polymer commonly used in the art for forming an organic-inorganic composite porous layer. g ) may be used because it can improve mechanical properties such as flexibility and elasticity of the organic-inorganic composite porous layer that is finally formed. Such a binder polymer effectively plays a role of binding and stably fixing inorganic particles to each other, thereby contributing to preventing deterioration of the mechanical properties of the separator having the organic-inorganic composite porous layer introduced therein.
[0056] In addition, the binder polymer does not necessarily have to have ion-conducting ability, but when a polymer having ion-conducting ability is used, the performance of the electrochemical element can be further improved. Therefore, the binder polymer can be used that has as high a dielectric constant as possible. In fact, since the degree of dissociation of salt in the electrolyte depends on the dielectric constant of the electrolyte solvent, the higher the dielectric constant of the binder polymer, the more the degree of dissociation of salt in the electrolyte can be improved. The dielectric constant of such a binder polymer can be in the range of 1.0 to 100 (measurement frequency = 1 kHz), and can be particularly 10 or more.
[0057] In addition to the above-mentioned functions, the binder polymer may have a feature of exhibiting a high degree of swelling in the electrolyte by gelling when impregnated with the liquid electrolyte. Therefore, the solubility index, i.e., Hildebrand solubility parameter, of the binder polymer is 15 to 45 MPa. 1 / 2 , 15~25MPa 1 / 2 Or 30 to 45 MPa 1 / 2 Therefore, it is more preferable to use a hydrophilic polymer having many polar groups than a hydrophobic polymer such as polyolefins. 1 / 2 Less than or 45MPa 1 / 2 If the content is excessive, it may be difficult for the battery to swell due to a typical liquid electrolyte.
[0058] Non-limiting examples of such binder polymers include polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP), polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polybutyl acrylate, polybutyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxymethyl cellulose.
[0059] Non-limiting examples of the inorganic particles include high dielectric constant inorganic particles having a dielectric constant of 5 or more, particularly 10 or more, inorganic particles having lithium ion transport ability, or a mixture thereof.
[0060] Non-limiting examples of inorganic particles having a dielectric constant of 5 or more include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT), Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, AlO(OH), Al2O3·H2O, or mixtures thereof.
[0061] In this specification, the term "inorganic particles having lithium ion transfer ability" refers to inorganic particles that contain lithium elements but do not store lithium and have the function of transferring lithium ions. Non-limiting examples of inorganic particles include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Tiy (PO4)3, where 0 < x < 2, 0 < y < 3, lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, where 0 < x < 2, 0 < y < 1, 0 < z < 3, (LiAlTiP) such as 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5 x O y system glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, where 0 < x < 2, 0 < y < 3), Li 3.25 Ge 0.25 P 0.75 S4 and other lithium germanium thiophosphate (Li x Ge y P z S w , where 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , where 0 < x < 4, 0 < y < 2), SiS2 - based glass (Li x Si y S z , where 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5 - based glass (Li x P y S z , where 0 < x < 3, 0 < y < 3, 0 < z < 7), or mixtures thereof, etc. can be mentioned.
[0062] According to one embodiment of the present invention, the organic - inorganic composite porous layer can be an organic coating layer using an organic slurry or an aqueous coating layer using an aqueous slurry. Among them, in the case of the aqueous coating layer, it is advantageous for thin - film coating and is further advantageous in terms of reducing the resistance of the separation membrane.
[0063] A separation membrane with enhanced stability having an organic - inorganic composite porous layer on at least one surface of a porous polymer substrate can be specifically manufactured as follows.
[0064] First, to form the organic-inorganic composite porous layer, a binder polymer is dissolved or dispersed in a dispersion medium, and then inorganic particles are added and dispersed to prepare a composition (slurry) for forming the organic-inorganic composite porous layer. The inorganic particles may be added in a state in which they have been crushed to have a predetermined average particle size, or the inorganic particles may be added to a mixture of the binder polymer and the dispersion medium, and then crushed and dispersed while controlling the inorganic particles to have a predetermined average particle size using a ball mill method or the like.
[0065] The composition for forming the organic-inorganic composite porous layer is coated on the porous polymer substrate. The coating method is not particularly limited, but it is preferable to use a slot coating method or a dip coating method. In the slot coating method, the composition supplied through a slot die is applied to the entire surface of the substrate, and the thickness of the coating layer can be adjusted according to the flow rate supplied from a metering pump. In addition, in the dip coating method, the substrate is immersed in a tank filled with the composition to coat it, and the thickness of the coating layer can be adjusted according to the concentration of the composition and the speed at which the substrate is pulled up from the composition tank. In order to control the coating thickness more accurately, the substrate may be post-weighed using a Mayer bar after immersion.
[0066] The porous polymer substrate coated with the composition for forming an organic-inorganic composite porous layer is dried using a dryer such as an oven to form an organic-inorganic composite porous layer on at least one surface of the porous polymer substrate.
[0067] In one embodiment of the present invention, the binder polymer may attach the inorganic particles to each other (i.e., the binder polymer connects and fixes the inorganic particles) so that the inorganic particles can be maintained in a state of being bound to each other, and the binder polymer may maintain the inorganic particles and the porous polymer substrate in a state of being bound to each other. The inorganic particles of the organic-inorganic composite porous layer may form an interstitial volume in a state of being substantially in contact with each other, and here, the interstitial volume means a space defined by inorganic particles that are substantially in contact with each other in a packed structure (closely packed or densely packed) of the inorganic particles. The interstitial volume between the inorganic particles may become an empty space and form pores of the organic-inorganic composite porous layer.
[0068] Non-limiting examples of the dispersion medium used here include one compound selected from acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone, methyl ethyl ketone, cyclohexane, methanol, ethanol, isopropyl alcohol, propanol, and water, or a mixture of two or more compounds.
[0069] In addition, in one embodiment of the present invention, the composition for forming the organic-inorganic composite porous layer is coated on the porous polymer substrate, and then the composition is dried at a temperature of 20 to 70° C. or 23 to 60° C. under a relative humidity of 30 to 80% or 50 to 80% for 1 minute to 2 hours, 5 minutes to 1 hour, or 10 minutes to 1 hour to remove the solvent, thereby finally producing a separator having an organic-inorganic composite porous layer on at least one surface thereof and having enhanced stability.
[0070] A separator obtained by coating and drying a slurry containing inorganic particles, a binder polymer, and a dispersion medium on at least one surface of the porous substrate classified as a good product to form an organic-inorganic composite porous layer may have excellent air permeability of 600 sec / 100 cc or less.
[0071] When the method for pre-detecting defects in a porous polymer substrate for a separation membrane according to an embodiment of the present invention is applied, the pre-detection result of pass / fail obtained by calculating the average value of the corrected pore distribution uniformity index in the state of the porous polymer substrate and comparing it with a reference value can completely correspond to the air permeability characteristics of a separation membrane having an organic-inorganic composite porous layer.
[0072] The present invention will be described in detail below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.
[0073] Manufacturing Example 1 (1) Manufacturing of porous polymer substrate A high density polyethylene having a weight average molecular weight of 350,000 (VH035, manufactured by Daehan Petrochemicals) was fed as a polyolefin at a rate of 9.0 kg / hr, and liquid paraffin oil (LP350F, 68 cSt, manufactured by Kyokuto Petrochemicals) was fed as a diluent at a rate of 21.0 kg / hr into the extruder and mixed.
[0074] In this case, the extruder is a twin-screw extruder having a hopper for feeding the polyolefin and the diluent, a kneading section for mixing the fed materials while transporting them, and a die outlet for extruding the mixed materials.
[0075] The polyethylene composition extruded by the extruder was molded into a sheet through a T-die and a cooling casting roll, and then biaxially stretched in a tenter-type sequential stretching machine for MD stretching (machine direction stretching, longitudinal stretching) followed by TD stretching (transverse direction stretching). The MD stretch ratio and TD stretch ratio were both 7.0 times. The stretching temperatures were 110°C in MD and 125°C in TD.
[0076] A polyolefin separator was manufactured by extracting the diluent from the stretched sheet with methylene chloride and heat-setting the sheet from which the diluent was extracted at a temperature of 126°C. In the heat-setting step, the sheet was stretched in the transverse direction to 40% of the width of the sheet introduced into the heat-setting step, and then relaxed to 15% to manufacture a porous polyolefin substrate (porous polymer substrate). The thickness of the porous polyolefin substrate manufactured in this case was 8.6 μm.
[0077] (2) Manufacturing of separation membranes with organic-inorganic composite porous layers PVdF-HFP (weight average molecular weight 390,000, HFP content 8% by weight) and PVDF-CTFE (polyvinylidene fluoride-chlorotrifluoroethylene copolymer) (weight average molecular weight 450,000, CTFE content 20% by weight) as binder polymers and cyanoethyl vinyl alcohol as dispersant (also acts as binder polymer) were added to acetone and dissolved at 50°C for about 12 hours or more to prepare a binder polymer solution. Alumina (Al2O3, average particle size 500nm) particles as inorganic particles were added to the prepared binder polymer solution and dispersed to prepare a slurry for the organic-inorganic composite porous layer. At this time, the weight ratio of PVdF-HFP, PVDF-CTFE, dispersant, coupling agent, and inorganic particles was 21:7:1:1:70.
[0078] The slurry for the organic-inorganic composite porous layer thus prepared was coated on both sides of a prepared porous polyolefin substrate by dip coating, and dried at 23° C. for 10 minutes under a relative humidity of 50% to prepare a separator having organic-inorganic composite porous layers on both sides (total thickness of both sides: about 6 μm).
[0079] Manufacturing Example 2 A porous polyolefin substrate was produced in the same manner as in Production Example 1, except that high density polyethylene having a weight average molecular weight of 350,000 (VH035, manufactured by Daehan Oil Chemical Co., Ltd.) and high density polyethylene having a weight average molecular weight of 600,000 (VH150U, manufactured by Daehan Oil Chemical Co., Ltd.) were fed into the extruder at rates of 7.0 kg / hr and 2 kg / hr, respectively. The thickness of the produced porous polyolefin substrate was 9.0 μm.
[0080] In addition, a separator having organic-inorganic composite porous layers on both sides (total thickness of both sides: about 6 μm) was prepared in the same manner as in Preparation Example 1, except that the thus-prepared porous polyolefin substrate was used.
[0081] Production Example 3 A porous polyolefin substrate was produced in the same manner as in Production Example 1, except that the TD stretching temperature was adjusted to 130° C. The thickness of the produced porous polyolefin substrate was 9.1 μm. Here, the TD stretching temperature of 130° C. was set to simulate a phenomenon in which the process temperature rose slightly due to problems with the intake and exhaust motor, heater, filter, etc. in the TD stretching section during mass production.
[0082] In addition, a separator having organic-inorganic composite porous layers on both sides (total thickness of both sides: 6 μm) was prepared in the same manner as in Preparation Example 1, except that the thus-prepared porous polyolefin substrate was used.
[0083] Production Example 4 The corrected average PDI was confirmed using a separator for process filters instead of a separator for lithium secondary batteries. This product had too large pores (average pore size 120nm, maximum pore size 140nm) and was therefore not suitable for use as a separator for secondary batteries.
[0084] The separation membrane for a process filter was produced by the following steps.
[0085] A fluororesin-containing composition was prepared by mixing 100 parts by weight of PTFE (polytetrafluoroethylene) resin 650J (registered trademark, manufactured by MCF) with 22 parts by weight of lubricant (Isopar H, manufactured by Exxon), and then aging at 38°C for 24 hours. A preform block was then prepared by applying a pressure of 4 MPa, and extruded into a sheet of 1 mm thickness using a paste extrusion device, and rolled to a thickness of 300 μm through calendaring to prepare a PTFE film. The prepared PTFE film was heat-treated in a heated oven at 200°C using a roll-to-roll process to completely remove the lubricant.
[0086] The heat-treated PTFE film was stretched 3 times in the machine direction at 300°C using a roll speed difference, and then a relaxation process was performed at 310°C by slowing down the roll speed so that 10% shrinkage occurred in the MD direction.
[0087] Then, the film was stretched 10 times in the transverse direction using a roll speed difference at 280° C., and the film was heat-set at 370° C. for 9 seconds using a heated roll to produce a PTFE porous membrane, which is a separator for a process filter.
[0088] Production Example 5 A porous polyolefin substrate was prepared in the same manner as in Preparation Example 1, except that the heat setting temperature was increased to 135° C. to simulate the temperature problem that occurs during heat setting. The thickness of the prepared porous polyolefin substrate was 8.7 μm. This separator could not be used for a secondary battery because the ventilation time was too long.
[0089] Proactive detection of defects in porous polyolefin substrates The porous polyolefin substrates produced in Production Examples 1 to 5 were first observed under conditions of 5 kV, 10 μA, and 20,000 magnification with a scanning electron microscope (SEM) (manufacturer: Hitachi, product name: S-4800) to obtain images of the porous polymer substrates. The SEM images of the porous polyolefin substrates produced in Production Examples 1 to 5 are shown in Figures 1a, 2a, 3a, 4a, and 5a, respectively.
[0090] The average value of the pore distribution uniformity index (PDI) was quantified using the obtained image of the porous polymer substrate. In this quantification step, the pixels of the raw image of the porous polymer substrate measured by scanning electron microscope (SEM) were divided into pixels representing a region of a plurality of polymer fibrils adjacent to each other or intersecting with each other and pixels representing a pore region formed between the plurality of polymer fibrils to obtain a 2-D binary image, and the 2-D binary image was distance transformed using a computer Euclidean distance transformation method. The results of the distance transformation of the porous polyolefin substrates manufactured in Preparation Examples 1 to 5 are shown in Figures 1b, 2b, 3b, 4b, and 5b, respectively.
[0091] A local maxima operation was applied to the distance transformed image to extract distance transformed values of all pixels of the image, and statistical processing was performed to obtain the average value of the quantified pore distribution uniformity index (average uncorrected PDI).
[0092] Thereafter, the average value of the quantified pore distribution uniformity index (uncorrected average PDI) was corrected to obtain the average value of the corrected pore distribution uniformity index (corrected average PDI).
[0093] [Formula 1] Corrected average PDI=Pre-correction average PDI×(1 / η) (In Equation 1, η is a correction factor, defined as η = (number of polymer fibril pixels) / (number of total image pixels).)
[0094] The average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrates prepared in Preparation Examples 1 to 5 and graphs of the corrected pore distribution uniformity index are shown in Figures 1c, 2c, 3c, 4c, and 5c, respectively.
[0095] Specifically, Figures 6a to 6d show raw images, 2D binary images, graphs of the average quantified pore distribution uniformity index (pre-corrected average PDI), and graphs of the average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrate produced in Preparation Example 1. Figures 7a to 7d show raw images, 2D binary images, graphs of the average quantified pore distribution uniformity index (pre-corrected average PDI), and graphs of the average corrected pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrate produced in Preparation Example 4.
[0096] Comparing the raw images and 2D binary images of the porous polyolefin substrates of Preparation Example 1 and Preparation Example 4 in Figures 6a to 6d and 7a to 7d, it can be seen that the pore regions (black regions in the 2D binary images) in Preparation Example 1 are uniformly dispersed and of a uniform size compared to Preparation Example 4. However, the pre-correction average PDI was similar at about 38 a.u. in both Preparation Examples 1 and 4. Then, the average corrected pore distribution uniformity index (corrected average PDI) showed a clear difference, with the porous polyolefin substrate of Preparation Example 1 at 39.46 au and the porous polyolefin substrate of Preparation Example 4 at 70.14 au.
[0097] This is because, referring to Figures 6a to 6d and 7a to 7d, in the case of Manufacturing Example 1, the area ratio of the white area (fiber) in the 2D binary image is larger than the area ratio of the white area in Manufacturing Example 4, and therefore the correction factor (η), which is the ratio of the number of fiber (white area) pixels to the number of total image pixels, also has a larger value for Manufacturing Example 1 (0.914) than for Manufacturing Example 4 (0.667).
[0098] Table 1 shows the average quantified pore distribution uniformity index (uncorrected average PDI), correction factor, and corrected average pore distribution uniformity index (corrected average PDI) of the porous polyolefin substrates produced in Production Examples 1 to 5.
[0099] The porous polyolefin substrates thus obtained, manufactured in Manufacturing Examples 1 to 5, were checked to see whether their average corrected pore distribution uniformity index (corrected average PDI) was 60 a.u. or less, and if it was 60 a.u. or less, it was classified as a good product, and if it was over 60 a.u., it was classified as a defective product. The results are also shown in Table 1.
[0100] How to evaluate air permeability (air permeability time) The air permeability (Gurley) of the porous polymer substrates and the separators having the organic-inorganic composite porous layers prepared in Preparation Examples 1 to 5 was measured according to the ASTM D726-94 method, and the results are shown in Table 1. The Gurley used here is the resistance to air flow and was measured using a Gurley densometer. The air permeability value described here is the value measured when 100cc of air is blown through 1 in of the porous polymer substrate or the separator under a pressure of 12.2 inH2O. 2 The time (seconds) required for a gas to pass through the cross section of the sample was defined as the aeration time.
[0101] [Table 1]
[0102] Referring to Table 1, the porous polymer substrates of Preparation Examples 1 and 2 satisfied the average corrected pore distribution uniformity index of 60 a.u. or less. Thus, the air permeability of the porous polymer substrate before the formation of the organic-inorganic composite porous layer was similar to that of Preparation Example 3, in which the average corrected pore distribution uniformity index exceeded 60 a.u., but the air permeability of the separator obtained after the formation of the organic-inorganic composite porous layer was about 210 to 220 seconds / 100cc, which was reduced by about 30% compared to the air permeability of the separator after the formation of the organic-inorganic composite porous layer using the porous polymer substrate of Preparation Example 3. From this, when the method for pre-detecting defective products of a porous polymer substrate for a separation membrane according to an embodiment of the present invention is applied, the average value of the pore distribution uniformity index after correction in the state of the porous polymer substrate is calculated and compared with the reference value, and the pre-detection result of pass / fail products obtained by comparing the average value with the reference value is confirmed to completely correspond to the air permeability characteristics of the separation membrane having an organic-inorganic composite porous layer. Therefore, compared with the conventional method of manufacturing a separation membrane having an organic-inorganic composite porous layer, evaluating the air permeability, classifying defective products, and discarding them, the pre-detection method of the present invention can detect defective products in advance at the stage of a porous polymer substrate, which is significantly advantageous in terms of time and cost.
Claims
1. Selecting a porous polymer substrate having a large number of pores to detect whether the substrate is good or bad; Obtaining an image of the selected porous polymer substrate by observing the selected porous polymer substrate with an electron microscope; Quantifying an average pore distribution uniformity index (PDI) using the acquired image of the porous polymer substrate; correcting the average value of the quantified pore distribution uniformity index to obtain an average value of the corrected pore distribution uniformity index; determining whether the average value of the corrected pore distribution uniformity index is 60 a.u. or less; If the average value of the corrected pore distribution uniformity index is confirmed to be 60 a.u. or less, the product is classified as a good product, and if the average value of the corrected pore distribution uniformity index is confirmed to be more than 60 a.u., the product is classified as a defective product, Quantifying the average value of the pore distribution uniformity index, obtaining a two-dimensional binary image by dividing the pixels of a raw image of the porous polymer substrate measured by an electron microscope into pixels representing a region of a plurality of polymer fibrils adjacent to or intersecting each other and pixels representing pore regions formed between the plurality of polymer fibrils; distance transforming the two-dimensional binary image using a computer Euclidean distance transform; applying a local maxima operation to the distance-transformed two-dimensional binary image to extract distance-transformed values of all pixels of the image, and statistically processing the distance-transformed values.
2. 2. The method for pre-detecting defects in a porous polymer substrate for a separation membrane according to claim 1, wherein the step of correcting the average value of the quantified pore distribution uniformity index (pre-correction average PDI) and obtaining the corrected average value of the pore distribution uniformity index (corrected average PDI) is calculated by the following Equation 1: [Formula 1] Corrected average PDI = average PDI before correction × (1 / η) In Equation 1, η is a correction factor and is defined as η=(number of polymer fibril pixels) / (number of total image pixels).
3. 3. The method for detecting defects in a porous polymer substrate for a separation membrane according to claim 1 or 2, wherein a separation membrane obtained by applying a slurry containing inorganic particles, a binder polymer, and a dispersion medium to at least one surface of the porous substrate classified as a non-defective product and drying the slurry to form an organic-inorganic composite porous layer has an air permeability of 600 sec / 100 cc or less.
4. 2. The method for pre-detecting defects in a porous polymer substrate for a separation membrane according to claim 1, wherein the average corrected pore distribution uniformity index is 40 a.u. or less and the average corrected pore distribution uniformity index is more than 40 a.u., the method is classified as a non-defective product.
Citation Information
Patent Citations
Method and device for inspecting flaw of porous thin plate
JP2005114418A
Automatic check method for appearance defect of continuous porous electrode base material and winding body of porous electrode base material with its recording medium
JP2010272250A
Surface inspection method and apparatus for perforated plate
JP2012107936A
Method for measuring pore distribution in secondary battery electrodes
JP2020507889A